2017
DOI: 10.1002/tea.21397
|View full text |Cite
|
Sign up to set email alerts
|

A construct-modeling approach to develop a learning progression of how students understand the structure of matter

Abstract: This paper builds on the current literature base about learning progressions in science to address the question, “What is the nature of the learning progression in the content domain of the structure of matter?” We introduce a learning progression in response to that question and illustrate a methodology, the Construct Modeling (Wilson, ) approach, for investigating the progression through a developmentally based iterative process. This study puts forth a progression of how students understand the structure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 33 publications
0
37
0
2
Order By: Relevance
“…Wright maps may also suggest that a new variable or a subdimension should be added to the LP. For example, Morell, Collier, Black, and Wilson () identified the existence of subcategories within a variable of their initial matter LP.…”
Section: Resultsmentioning
confidence: 99%
“…Wright maps may also suggest that a new variable or a subdimension should be added to the LP. For example, Morell, Collier, Black, and Wilson () identified the existence of subcategories within a variable of their initial matter LP.…”
Section: Resultsmentioning
confidence: 99%
“…Although the relevance of fundamental concepts have been emphasized for many years, research on students' understanding has consistently shown that students' fail to obtain a deeper understanding even of the most fundamental concepts, for instance the particulate nature of matter (Löfgren & Helldén, ; Morell, Collier, Black, & Wilson, ; Stefani & Tsaparlis, ), chemical reaction (cf., Talanquer, ; Taskin & Bernholt, ), or energy (cf., Herrmann‐Abell & DeBoer, ; Neumann, Viering, Boone, & Fischer, ). Thus, it remains an open question to which extent school science enables students to develop a sophisticated understanding of fundamental concepts in the domain and which learning gains can be expected from year to year (Bloom, Hill, Black, & Lipsey, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The outcome is a map of the interlinking of many component concepts which can be used as a guide for teachers' planning. Such maps have been produced by work in England (Johnson & Tymms, 2011), Germany (Hadenfeldt, Neumann, Bernholt, & Liu, 2016) and the US (Morell, Collier, Black, & Wilson, 2017). In general, state curricula only provide a general and partly hypothetical basis on which teachers choose a progression sequence in promoting students' learning.…”
Section: Assessment As An Intrinsic Part Of Classroom Activitymentioning
confidence: 99%